Relationship between Uric Acid to High Density Lipoprotein Cholesterol Ratio and Nonalcoholic Fatty Liver Disease in Nonoverweight/Obese Patients with Type 2 Diabetes - Yuliang Cui; Zhenzhen Qu; Wenmei Hu; Haiyan Shi (International Journal of Endocrinology)
Aims. To investigate the relationship between uric acid to high-density lipoprotein cholesterol ratio (UHR) levels and nonalcoholic fatty liver disease (NAFLD) in nonoverweight/obese patients with type 2 diabetes. Methods. A retrospective study was designed including a total of 343 inpatients with type 2 diabetes whose BMI<24 kg/m2. The population was divided into three groups as the UHR tertiles. Logistic regression analysis was performed to estimate odds ratios (ORs) of UHR for NAFLD. ROC curve analysis was used to estimate the diagnostic value of UHR for NAFLD. Results. The prevalence rat of NAFLD enhanced progressively from the tertile 1 to tertile 3 of UHR (30.70% vs. 56.52% vs. 73.68%). Logistic regression analysis showed that participants in the higher UHR groups, compared with those in the first tertile group, had higher occurrence risks for NAFLD. The positive association between UHR and NAFLD was independent of age, BMI, blood pressure, hepatic enzymes, and other components of metabolic disorders. ROC curve analysis showed that the area under curve (AUC), sensitivity, and specificity for UHR were 0.697, 0.761, and 0.553, respectively. Conclusions. In type 2 diabetic patients without overweight or obesity, UHR is significantly associated with NAFLD and can be used as a novel and useful predictor for NAFLD onset.